Conventional educational board games / Dr Tuan Sarifah Aini Syed Ahmad ... [et al.] - Syed Ahmad, Tuan Sarifah Aini; Zainal Abidin, Nur Amirah Nabihah; Md Sallehuddin, Nur Hakimah; Hassan, Fatin Aliyah (UiTM Cawangan Negeri Sembilan, 2022)
Have you played Scrabble before? It is an example of a conventional board game which is played for educational purposes in order to test English vocabulary. It has a set of rules in which players have to start a new word at a specific place on the board. It also has a winning state to determine the winner at the end of the game. Another interesting fact about Scrabble is the players will feel challenged to create words with the alphabet tiles they have to obtain the highest score. The challenge may create fun in playing Scrabble. Thus, any conventional educational board games should not only be fun and interesting for the players, but it needs to be educational.